The importance of spirituality in the implementation of democratic reforms in new Uzbekistan - Sagindikov DJubatxan Nawirzovich; Baynazarova Dilbar Allabay qizi (Zien Journals, 2024)
This article provides information about the importance of spirituality and the role of the concept of spirituality in the implementation of democratic reforms in New Uzbekistan. In it, the content and essence of spiritual thinking in the upbringing of young people and their growing up as perfect people in the future were discussed in detail. Wide discussions are taking place in our country about the opportunities created for our youth and the measures being taken to effectively spend their free time. The essence and quality of our national traditions, national values, and ancient history were explained in order to raise the spirituality of young people and bring them up as perfect people. In this great country, dear person, attention to the future of our motherland is attention to the future of our country, its people and, of course, the nation. State awards were established for our young people who take the initiative in implementing the state youth policy.
Keywords: Spirituality; democratic reforms; future generation